Isotope Engineered Fluorinated Single and Bilayer Graphene: Insights into Fluorination Selectivity, Stability, and Defect Passivation. Issue 12 (2nd January 2023) - Thakur, Mukesh Kumar; Haider, Golam; Sonia, Farjana J.; Plšek, Jan; Rodriguez, Alvaro; Mishra, Vipin; Panda, Jaganandha; Gedeon, Ondrej; Mergl, Martin; Volochanskyi, Oleksandr; Valeš, Václav; Frank, Otakar; et al.
Abstract: Tailoring the physicochemical properties of graphene through functionalization remains a major interest for next‐generation technological applications. However, defect formation due to functionalization greatly endangers the intrinsic properties of graphene, which remains a serious concern. Despite numerous attempts to address this issue, a comprehensive analysis has not been conducted. This work reports a two‐step fluorination process to stabilize the fluorinated graphene and obtain control over the fluorination‐induced defects in graphene layers. The structural, electronic and isotope‐mass‐sensitive spectroscopic characterization unveils several not‐yet‐resolved facts, such as fluorination sites and CF bond stability in partially‐fluorinated graphene (F‐SLG). The stability of fluorine has been correlated to fluorine co‐shared between two graphene layers in fluorinated‐bilayer‐graphene (F‐BLG). The desorption energy of co‐shared fluorine is an order of magnitude higher than the CF bond energy in F‐SLG due to the electrostatic interaction and the inhibition of defluorination in the F‐BLG. Additionally, F‐BLG exhibits enhanced light–matter interaction, which has been utilized to design a proof‐of‐concept field‐effect phototransistor that produces high photocurrent response at a time <200 µs. Thus, the study paves a new avenue for the in‐depth understanding and practical utilization of fluorinated graphenic carbon. Abstract : Due to the extraordinary mass sensitivity of phonon‐energy in graphene, isotopically‐labeled layers provide a unique platform for probing physicochemical properties of chemically‐tailored‐graphene in nanoscale, which otherwise remains a great challenge. This study on 12 C and 13 C isotope‐based fluorinated bilayer graphene unveils fluorination sites, selectivity and stability, providing a way to produce tailored‐graphene for high‐performance nano‐optoelectronic devices.